Pre-depulping and depulping treatments and the emergence of queen palm seeds (Syagrus romanzoffiana [Cham.] Glassman) - Nascimento, Lucas Marquezan; Vendruscolo, Eduardo Pradi; Campos, Luiz Fernandes Cardoso; Garcia, Lismaíra Gonçalves Caixeta; Pires, Larissa Leandro; Seleguini, Alexsander (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The propagation of the palm Syagrus romanzoffiano is done sexually with seeds, making the process of obtaining new plants slow and difficult, especially on large scales. In addition, seed germination is slow, uneven and susceptible to degradation and loss of vigor because of embryo deterioration, even under laboratory conditions. As a result of the lack of information on efficient depulping methods for queen palm fruits, the present study aimed to establish a depulping methodology that is less aggressive to embryos, maintaining emergence quality. This experiment was carried out in Goiânia, Brazil, using fruits from eight stock plants submitted to three pre-depulping treatments (control, fermentation and drying) and two depulping methods (industrial depulping and concrete-mixer with the addition of gravel). After the different pre-sowing processes, the fresh and dry pyrenes mass, remaining fibers adhered to the pyrene and seedling emergence were evaluated. The pulper removed an average of 45% more pyrene pulp than the concrete mixer. However, these methodologies did not result in differences in the emergence of plants, which was affected only by the pre-depulping treatment, with superiority in the use of fresh fruits. Thus, the pulper was more efficient for the removal of pulp and pulp fibers than the concrete mixer. The depulping method did not significantly affect the pyrenes mass. Higher seedlings emergence values were observed for the fresh fruits that were pulped and sown immediately. Fermentation and partial pulp dehydration exert a negative influence on seedling emergence.